Spectroscopic study of metal-rare gas complexes and the vibrational dynamics of para-fluorotoluene - Withers, Carolyn Dawn (2012)
This work contains two main areas of research within the field of bonding and spectroscopy. The first is the interactions of metals and metal ions with rare gas atoms; the second concerns vibrational dynamics in para-fluorotoluene(pFT). The research has been carried out as part of a collaboration between the SOCAR and Reid groups at the University of Nottingham and also involved external research teams.